2007
DOI: 10.1007/s12034-007-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Redox ratio and optical absorption of polyvalent ions in industrial glasses

Abstract: The changes in glass structure and redox ratio, R (reduced ion to oxidized ion) of Mn 2+ -Mn 3+ , Cu + -Cu 2+ , Cr 3+ -Cr 6+ , Ni 2+ -Ni 3+ and Co 2+ -Co 3+ couples and optical absorption due to Mn 3+ , Cu 2+ , Cr 3+ , Ni 2+ and Co 2+ ions in industrial soda-lime-silica glass were investigated as a function of Na 2 O concentration in the range 11-19 mol%. With increasing Na 2 O concentration in the experimental glasses, the basicity, expressed as calculated basicity, Λ cal , increased. 29 Si NMR and X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…The characteristic large band of the reproduced glasses are shifted at higher 2θ angles with respect to the value of 21.5°found for the pure amorphous silica, where all the SiO 4 tetrahedra are connected through bridging oxygens (BO) (presence of only Q 4 units) [44][45][46][47][48]. Even if the exact relationship between the peak position and MRO is still widely debated in literature [40][41][42][43], the 2θ increase with potassium content (Fig.…”
Section: Xrpdmentioning
confidence: 93%
“…The characteristic large band of the reproduced glasses are shifted at higher 2θ angles with respect to the value of 21.5°found for the pure amorphous silica, where all the SiO 4 tetrahedra are connected through bridging oxygens (BO) (presence of only Q 4 units) [44][45][46][47][48]. Even if the exact relationship between the peak position and MRO is still widely debated in literature [40][41][42][43], the 2θ increase with potassium content (Fig.…”
Section: Xrpdmentioning
confidence: 93%
“…Other studies report the dissolution of chromium oxides in glass melts [6][7][8][9][10][11]. The authors have demonstrated that the solubility of chromium oxide strongly depends on glass basicity (melt composition), temperature and oxygen fugacity [6][7][8]12]. This latter parameter influences the redox properties of the glass and yields to the stabilization of high or low oxidation states of the multivalent elements in the melt.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive investigations on the infrared, Raman, optical absorption, luminescence and electron spin resonance spectroscopy of different transition metal ions in a variety of inorganic glasses have been made in the recent years in view of their technological applications [28][29][30][31][32]. Transition metal ions are known to influence the optical, electrical and magnetic properties of glasses due to their high sensitive response to the changes in the surrounding actions.…”
Section: Introductionmentioning
confidence: 99%